2012
DOI: 10.1016/j.neuropsychologia.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Pattern separation deficits following damage to the hippocampus

Abstract: Computational models of hippocampal function propose that the hippocampus is capable of rapidly storing distinct representations through a process known as pattern separation. This prediction is supported by electrophysiological data from rodents and neuroimaging data from humans. Here, we test the prediction that damage to the hippocampus would result in pattern separation deficits by having memory-impaired patients with bilateral hippocampal damage study a series of objects or faces and then perform a modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
38
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(44 citation statements)
references
References 51 publications
(58 reference statements)
6
38
0
Order By: Relevance
“…Through extensive testing, we have previously demonstrated that the lures have a controlled range of false alarm rates when used during recognition tests (Yassa et al, 2011a; Stark et al 2013; 2015). In addition, performance on these similar lures is sensitive to hippocampal damage (Kirwan et al, 2012), aging (Stark et al, 2013; 2015; Toner et al, 2009) and to the age-related changes in both the activity of the dentate gyrus and CA3 subfields during aging (Yassa et al, 2011b), and to disruptions of hippocampal circuitry (Yassa et al, 2011b; Bennett et al, 2015). Together, these findings demonstrate the viability of this task as a sensitive and appropriate measure of age-related memory change and of hippocampal function.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through extensive testing, we have previously demonstrated that the lures have a controlled range of false alarm rates when used during recognition tests (Yassa et al, 2011a; Stark et al 2013; 2015). In addition, performance on these similar lures is sensitive to hippocampal damage (Kirwan et al, 2012), aging (Stark et al, 2013; 2015; Toner et al, 2009) and to the age-related changes in both the activity of the dentate gyrus and CA3 subfields during aging (Yassa et al, 2011b), and to disruptions of hippocampal circuitry (Yassa et al, 2011b; Bennett et al, 2015). Together, these findings demonstrate the viability of this task as a sensitive and appropriate measure of age-related memory change and of hippocampal function.…”
Section: Methodsmentioning
confidence: 99%
“…For example, our lab developed a Mnemonic Similarity Task (MST; formerly BPS-O) that assesses a participants’ ability to discriminate between previously viewed objects (i.e., targets), similar lure objects, and unrelated foil objects (Kirwan & Stark, 2007; Yassa et al, 2011a, 2011b; Kirwan et al, 2012; Stark et al, 2013, 2015). The ability to discriminate between targets and similar lures has been shown to be impaired in healthy older adults, with an apparent sparing of their ability to discriminate between targets and unrelated foils (Toner et al, 2009; Yassa et al, 2011a, 2011b; Stark et al, 2013, 2015; Bennett et al, 2015; Reagh et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The total percent of correctly identified items at the delay was analyzed as the primary outcome (i.e., total correct/total trials; possible range: 0%–100%), controlling for response bias. The BPS-O demonstrates robust activation with the MTL in functional MRI paradigms (Law et al, 2005; Yassa et al, 2011) and has been validated to detect age-related memory changes in older adults (Yassa et al, 2011) and hippocampal specific injury (Kirwan et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Using the MST, we have reported a linear decline in lure discrimination performance across the lifespan, identifying similar lure items as “similar” (mnemonic discrimination), with no corresponding decrease in recognition for identifying repeated items as “old” (traditional recognition memory) [10] - a pattern which has also been shown in studies comparing groups of younger and older adults [11-13]. Additionally, performance on these lure trials is substantially impaired in patients with overt hippocampal damage relative to healthy controls [14] and is sensitive to individual differences in memory ability within aging (e.g. healthy older adults categorized as impaired vs. unimpaired relative to young, as “super-agers” vs. typical agers, etc.)…”
Section: Introductionmentioning
confidence: 98%